Termite colonies (Macrotermes michaelseni), tree locations and metrics of 2007 and 2019 in Namibia - Benjamin Wildermuth; Jens Oldeland; Norbert Jürgens (PANGAEA, 2021)
This data set contains metrics and coordinates of termite mounds (Macrotermes michaelseni) and associated trees in 1 km2 of Namibian thornbush savanna. Furthermore, all locations of Boscia albitrunca above 1.5 m height within the observatory are listed. Apart from the mound metrics, mound activity status and number of associated trees are provided. For the associated trees we provide data on the species, metrics and the relative position to the termite mound, respectively the coverage by the canopy. Out of all 362 analyzed termite mounds, 203 (56.08 %) were associated with a tree. Mounds with associated trees showed increased activity, growth and height. Mound growth within the study period was correlated positively with the canopy coverage by the associated tree whilst total mound heights were correlated non-linear with medium canopy coverage of about 40 %. Mounds with a tree covering the sun extquotesingles average zenith (north) were taller, grew most within 12 years and were more likely to be active than those with no northern canopy coverage. Mounds associated with the evergreen Boscia albitrunca attained highest average height (195.06 ± 11.76 cm). Therefore, we used the term “partner tree” for trees associated with Macrotermes michaelseni mounds. The mound metrics have been recorded in 2007 and 2019 and the trees were recorded and measured in 2019. The study observatory “Otjiamongombe” is located in Central Namibia, 120 km north of Windhoek and part of the BIOTA Africa project (Biodiversity Monitoring Transect Analysis). We mapped the observatory twice in order to get temporal data on mound metrics and dynamics with special regard to the associated vegetation. The data on tree parameters and tree distribution allow us to investigate the mutualism between termite mounds and partner trees. All locations were recorded with a handheld GPS (Garmin, Schaffhausen, Switzerland), having an accuracy of ± 3 m. We considered termite mounds as visible above ground mounds and also any presence of remnants of the outwash pediment. Measurements were taken with a measuring tape or stick and in case of large mounds and trees we used a Vertex IV tree height measuring instrument (Haglöf, Långsele, Sweden). Only trees directly adjacent to the termite mounds where measured and defined as partner trees. Mounds with proof of recent building activity were recorded as active.